IMPLEMENTASI SCM (SUPPLY CHAIN MANAGEMENT) PADA PENJUALAN ARLOJI DAN ASSESORIS BERBASIS WEB (STUDI KASUS : TOKO HIKMAH JAYA RECORD) - Tedi Rijali Rijali (NUANSA INFORMATIKA, 2016)
Supply Chain Management includes work environment and a broad responsibility. The procurement is one of the main components of SCM. The efficiency in procurement can provide a significant contribution in increasing the volume of the profitin a business sales. The procurement always needs the help of all technology business process. By selecting and implementing suitable technology, it can serve the goal of SCM. The wisdom of Jaya Record (HJR) is the of selling watches for the mid-level, where it has not had a business application for data processing. On the procurement activities, company chooses suppliers who can provide goods with the price and quality in accordance with the desired to get positive values for management stores and customers, it is expected that this new system can improve the quality of information that is useful for the respective institution